Pemikiran Pendidikan Syekh Nawawi Al-Bantani - Nabila Izzatin Farikhatun Naida; Tafrikhan T; Muhtar Sofwan Hidayat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Modern education, which tends to prioritize cognitive achievement, often neglects values education, thereby contributing to the phenomenon of moral degradation among students, particularly at the primary education level. This study aims to explore and contextualize the relevance of Shaykh Nawawi al-Bantani's educational thought as an alternative solution to the ethical crisis in the era of disruption. The research employs a qualitative approach using library research. The data are derived from the authentic works of Shaykh Nawawi, which are analyzed through content analysis and a historical-philosophical approach. The findings reveal that Shaykh Nawawi's educational paradigm places tazkiyat al-nafs (purification of the soul) and the cultivation of adab (proper moral conduct) as the fundamental prerequisites before the transmission of knowledge takes place. This paradigm is supported by a tawhid-based curriculum, the exemplary moral conduct and professional ethics of teachers as murabbi (educator-mentors), and the consistent application of habituation methods in the learning process. In conclusion, Shaykh Nawawi's educational thought remains highly relevant for integration into the hidden curriculum within the primary school (SD/MI) educational ecosystem. This study contributes to enriching the body of knowledge on Indonesian Islamic pedagogy while also providing practical strategic guidance for educators in designing a holistic character education ecosystem aimed at strengthening the moral character of future generations.